A report on the effects of wind speed on timber construction - Huenefeld, Joshua (Kansas State University, 2012)
Main lateral force resisting systems (MLFRS) in timber buildings consist of two components: diaphragms and shear walls. Diaphragms are used to collect the shear induced by the lateral force at each of the levels. The shear is transferred from the diaphragms to the shear walls via plywood sheathing and connections. The shear walls transfer shear to the sill plate via plywood sheathing and then into the foundation via anchors. Two approaches for designing shear wall are: the segmented shear wall approach and the perforated shear wall approach. The segmented shear wall approach uses only full height segments to resist shear; each individual segment must be designed to resist the shear and overturning force induced by the lateral load. The perforated shear wall approach uses both full height segments and segments around openings to resist shear; the wall as a whole is used to resist shear and overturning forces induced by the lateral load. This report examines one-, two-, and three-story timber buildings located in three different wind regions: a) 115 mph, b) 140 mph, and c) 160 mph. This report presents the design process for the MLFRS components and a comparison of the designs for each of the buildings. The purpose of this report is to determine how the design changes depending on the magnitude of the lateral load, the height of the building, and the approach used to design the shear walls.
Keywords: Timber; Diaphragm; Shearwall; Lateral; Wood; Building; Engineering (0537)